Implementation of Early Childhood Scientific Learning through Float and Sink Game - Munawaroh, Hidayatu (Universitas Negeri Semarang, 2015)
The research is motivated by scientific learning which was given by the teacher was less attractive, monotonous, even using the manufactured game and toy that tended to be practical. The purpose of this research is to know how the scientific learning implementation through float and sink game in learning. The type of the research is descriptive research which uses a qualitative approach. The result of the research is about the given scientific learning by the teacher has adjusted with the theme and the sub-theme, the method which is used by the teacher in scientific learning has been able to develop the scientific ability of children such as using experiment method. The obstacle is the teachers’ creativeness in designing scientific activity.How to citeMunawaroh, H. (2015). Implementation of Early Childhood Scientific Learning through Float and Sink Game. Indonesian Journal of Early Childhood Education Studies, 4(2), 70-74. doi:10.15294/ijeces.v4i2.9458DOI 10.15294/ijeces.v4i2.9458